FRI0213 RANDOMIZED PLACEBO CONTROLLED TRIAL OF ABATACEPT FOR NON-ORGAN THREATENING SYSTEMIC LUPUS WITH BACKGROUND MEDICATIONS WITHDRAWN. (June 2019) - Thanou, Aikaterini; Arriens, Cristina; Aberle, Teresa; Chakravary, Eliza; Vaseer, Samera; Rawdon, Joe; James, Judith A.; Merrill, Joan
Abstract : Background: Abatacept (ABA) is a fusion protein of the extracellular domain of CTLA4 and the Fc domain of human IgG1, constructed to inhibit B/T cell co-stimulation. Previous studies of ABA in lupus failed to show benefit in overall disease activity, but improvement in arthritis was suggested. Objectives: This 6-month randomized, double-blind, placebo-controlled (PBO) study withdrew background medications to facilitate the assessment of ABA in patients with SLE arthritis. Methods: Patients were entered with moderate to severe arthritis [BILAG A or B with ≥3 swollen and ≥3 tender joints (28 joint count)]. All DMARDs except prednisone (up to 20mg daily) were withdrawn by baseline and patients were randomized 1:1 to weekly sc ABA or PBO. One or more DepoMedrol injections (≤320mg total) was allowed by end of Month 2. Additional steroids or immune suppressants (IMS) at any time, and transition to open label ABA at Month 3 or later, were allowed, but designated non-response. The primary endpoint was BICLA response at Month 6 compared to screening. Secondary objectives included SRI-4, SLEDAI 4-point improvement, SLEDAI arthritis resolution, BILAG A/B musculoskeletal (MSK) improvement, as well as low disease activity defined by either SLEDAI 2 or Lupus Low Disease Activity State (LLDAS) at Month 6. Flares were evaluated by the modified SELENA-SLEDAI flare index (1) in patients followed after baseline. Results: 66 patients were randomized and received at least one dose of the study drug, 31 ABA and 35 PBO. 7 withdrew prior to Month 6. Placebo response rates were lower than in most SLE trials, but no primary or secondary endpoints were met, see table (Fischer's exact test). Flares were evaluable in 64 patients (31 on ABA, 33 on PBO). 14 (45%) patients on ABA vs. 18 (55%) on PBO had a moderate/severe flare by Month 6. 22 (71%) patients on ABA vs. 23 (70%) on PBO experienced flare or treatment failure (early drop off or off protocol steroids or IMS) by Month 6. Rates of flare and treatment failure by Month 6 did not differ between groups (Log-Rank test, p=0.688 and p=0.631, respectively). The safety profile of ABA was consistent with known effects of the treatment. Conclusion: ABA did not demonstrate improvement vs placebo in controlling disease activity or flare in SLE patients in a protocol that mandated IMS withdrawal. Placebo response rates of ≤23% support the validity of these results. Since some evidence suggests potential efficacy of ABA for certain biologic subsets of SLE (2), immunophenotyping may prove helpful. References: [1] Thanou A, Chakravarty E, James JA, Merrill JT. Rheumatology (Oxford) 2014;53(12):2175-81. [2] Bandyopadhyay S, Connolly SE, Jabado O, Ye J, Kelly S, Maldonado MA, Westhovens R, Nash P, Merrill JT, Townsend RM. Lupus Sci Med. 2017 4 (1): e000206. Disclosure of Interests: Aikaterini Thanou Grant/research support from: Bristol-Myers Squibb, Consultant for: Neovacs, Cristina Arriens Grant/research support from: Bristol-Myers Squibb, GSK/HGS, Consultant for: GSK, AstraZeneca, Teresa Aberle: None declared, Eliza Chakravary: None declared, Samera Vaseer: None declared, Joe Rawdon: None declared, Judith A. James: None declared, Joan Merrill Grant/research support from: Genentech, UCB, GSK, EMD Serono, Pfizer, Celgene, Exagen, Bristol Myers Squibb, Medimmune/Astra Zeneca, Lilly, Amgen, Xencor, Neovacs, Consultant for: Genentech, UCB, GSK, EMD Serono, Pfizer, RemeGen, Celgene, Exagen, Bristol Myers Squibb, Medimmune/Astra Zeneca, Lilly, Immupharma, Amgen, Janssen, Sanofi, Neovacs, Anthera, Speakers bureau: UCB, GSK, EMD Serono, Bristol Myers Squibb, Medimmune/Astra Zeneca, Janssen